Targetome analysis of chaperone-mediated autophagy in cancer cells. Issue 9 (2nd September 2019) - Hao, Yuqing; Kacal, Merve; Ouchida, Amanda Tomie; Zhang, Boxi; Norberg, Erik; Vakifahmetoglu-Norberg, Helin
ABSTRACT: Chaperone-mediated autophagy (CMA) is a lysosomal degradation pathway of select soluble proteins. Nearly one-third of the soluble proteins are predicted to be recognized by this pathway, yet only a minor fraction of this proteome has been identified as CMA substrates in cancer cells. Here, we undertook a quantitative multiplex mass spectrometry approach to study the proteome of isolated lysosomes in cancer cells during CMA-activated conditions. By integrating bioinformatics analyses, we identified and categorized proteins of multiple cellular pathways that were specifically targeted by CMA. Beyond verifying metabolic pathways, we show that multiple components involved in select biological processes, including cellular translation, was specifically targeted for degradation by CMA. In particular, several proteins of the translation initiation complex were identified as bona fide CMA substrates in multiple cancer cell lines of distinct origin and we show that CMA suppresses cellular translation. We further show that the identified CMA substrates display high expression in multiple primary cancers compared to their normal counterparts. Combined, these findings uncover cellular processes affected by CMA and reveal a new role for CMA in the control of translation in cancer cells. Abbreviations: 6-AN: 6-aminonicotinamide; ACTB: actin beta; AR7: atypical retinoid 7; CHX: cycloheximide; CMA: chaperone-mediated autophagy; CQ: chloroquine; CTS: cathepsins; DDX3X: DEAD-box helicase 3 X-linked; EEF2: eukaryotic translation elongation factor 2; EIF4A1: eukaryotic translation initiation factor 4A1; EIF4H: eukaryotic translation initiation factor 4H; GEO: Gene Expression Omnibus; GO: Gene Ontology; GSEA: gene set enrichment analysis; HK2: hexokinase 2; HSPA8/HSC70: heat shock protein family A (Hsp70) member 8; LAMP: lysosomal-associated membrane protein; LDHA: lactate dehydrogenase A; NES: normalized enrichment score; NFKBIA: NFKB inhibitor alpha; PCA: principle component analysis; PQ: paraquat; S.D.: standard deviation; SUnSET: surface sensing of translation; TMT: tandem mass tags; TOMM40/TOM40: translocase of outer mitochondrial membrane 40.